Development and economic evaluation of a pharmacist-provided chronic care management service in an ambulatory care geriatrics clinic. (15th November 2018) - Fixen, Danielle R.; Linnebur, Sunny A.; Parnes, Bennett L.; Vejar, Maria V.; Vande Griend, Joseph P.
Abstract : Purpose: The implementation and delivery of a pharmacist-led chronic care management (CCM) service in a geriatric primary care clinic are described. Methods: A CCM service was provided March 1 through December 31, 2016, at the University of Colorado Hospital Seniors Clinic ("Seniors Clinic"). The electronic health record (EHR) team for the University of Colorado Health system developed a patient registry through EPIC Healthy Planet (Epic Systems Corp., Verona, WI) to identify patients at the Seniors Clinic eligible for CCM services. The EHR team constructed a note type and documentation template within the EHR to ensure documentation of all necessary components for billing and to allow individual clinical staff to document the time spent providing CCM care. Results: Overall, 36 elderly patients enrolled in the pharmacist-provided CCM service over the 10 months. Clinical pharmacists spent a total of 156–849 minutes per month providing CCM services, with a mean outreach time of 45.4 minutes per patient. The clinical pharmacists submitted 95 claims, and all but 5 were paid. The total amount reimbursed from the health plans during the 10 months was 2, 775.02. Conclusion: Medicare patients were successfully enrolled in a CCM service in a geriatrics primary care clinic led by clinical pharmacists and medical providers. The CCM services were more time-consuming than the allotted 20 minutes per patient per month with the CCM Current Procedural Terminology code used during this study.